Extraction of Essential Oils from Citrus By-Products Using Microwave Steam Distillation - Shakir, Ibtehal K.; Salih, Sarah J. (Iraqi Journal of Chemical and Petroleum Engineering, 2015)
The main objectives of this research is to extract essential oil from: orange ( citrus sinensis), lemon( citrus limon) and mandarin( citrus reticulata) peels by two methods: steam distillation (SD) and microwave assisted steam distillation (MASD), study the effect of extraction conditions (weight of the sample, extraction time, and microwave power, citrus peel type) on oil yield and compare the results of the two methods, the resulting essential oil was analyzed by Gas Chromatography (GC).   Essential oils are highly concentrated substances used for their flavor and therapeutic or odoriferous properties, in a wide selection of products such as foods, medicines and cosmetics. Extraction of essential oil is one of the most time and effort consuming process. Microwave-assisted extraction is a green technique for the extraction of natural products. (MASD) was better than (SD) in terms of rapidity, energy saving and yield. (MASD) gave higher yield than (SD) with shorter extraction time, yield of orange oil extracted by (MASD) was (1.150%) in (35min.) compared to (1.095%) in (45min.) by (SD) process, same results obtained for lemon and mandarin.   The optimal microwave power was (135W) gave oil yield: (1.150%, 1.115%, 0.940%) for orange, lemon and mandarin respectively, (MASD) increased extraction temperature in short time and to a higher level compared to (SD). The optimal weight was (398.56gm) gave yield in (SD): (1.095%) and MASD (1.091%) for orange oil, same results obtained for lemon and mandarin. The best citrus peel type which gave the highest yield was orange followed by lemon then mandarin in both processes.Limonene is the most abundant component in citrus essential oil, (GC) analysis showed that (SD) was more convenient to give high amount of limonene because of the graduate temperature rise, while in microwave extraction exposure to low microwave